HUBUNGAN PEMENUHAN ASUH DENGAN STATUS GIZI LEBIH PADA ANAK SEKOLAH - Lili Kurniawati; Kristiawati Kristiawati; Aria A. Nastiti (Universitas Airlangga, 2014)
Introduction: Indonesia as a developing country has many nutritional problems that a blend of malnutrition and overnutrition problem with the prevalence of obesity that increase every year. Obesity is the effect of imbalance between energy intake that exceeds expenditure energy. The purpose of this research is to analyze the relation between base requirement (foster) with overnutrition status in school age children.Methods: The design of the study was descriptive analytic with cross-sectional approach. The population was all of students in the elementary school of Sumberpucung 03 Malang with over nutrition status. The sampling technique used purposive sampling with 53 respondents. The data aggregation used quisioner and analyzed with spearman rho correlation test with p <0.05 signification degrees.Results: The result of analyze showed a significant correlation between the compliance of nutrient requirement (p=0.003; r=0.397) and it has relation with the compliance of physic activity of children (p=0.003; r=0.398) with overnutrition status.Conclusion: Compliance of basic requiremant (Foster): nutrition and physical activity has a positive relationship with overnutrient status that means the better compliance of diet and physical activity levels, the lower overnutrition status of school age children, so parents are expected can fullfill the nutrition and good activity to prevent overnutrition status in children